Chronic exposure to traffic-related air pollution and cancer incidence among 10, 000 patients undergoing percutaneous coronary interventions: A historical prospective study. (29th August 2020) - Cohen, Gali; Levy, Ilan; Yuval,; Kark, Jeremy D; Levin, Noam; Witberg, Guy; Iakobishvili, Zaza; Bental, Tamir; Broday, David M; Steinberg, David M; Kornowski, Ran; Gerber, Yariv
Abstract: Background: Exposure to traffic-related air pollution (TRAP) is considered to have a carcinogenic effect. The authors previously reported a nonsignificant association between TRAP and cancer risk in a relatively small cohort of myocardial infarction survivors. This study assessed whether TRAP exposure is associated with subsequent cancer in a large cohort of coronary patients. Methods & results: Consecutive patients undergoing percutaneous coronary interventions in a major medical centre in central Israel from 2004 to 2014 were followed for cancer through 2015. Residential levels of nitrogen oxides (NOx ) – a proxy for TRAP – were estimated based on a high-resolution national land use regression model. Cox proportional hazards models were constructed to study relationships with cancer. Among 12, 784 candidate patients, 9816 had available exposure data and no history of cancer (mean age, 68 years; 77% men). During a median (25th–75th percentiles) follow-up of 7.0 (3.9–9.3) years, 773 incident cases of cancer (8%) were diagnosed. In a multivariable-adjusted model, a 10-ppb increase in mean NOx exposure was associated with hazard ratios (HRs) of 1.07 (95% confidence interval [CI] 1.00–1.15) for all-site cancer and 1.16 (95% CI 1.05–1.28) for cancers previously linked to TRAP (lung, breast, prostate, kidney and bladder). A stronger association was observed for breast cancer (HR = 1.43; 95% CI 1.12–1.83). Associations were slightly strengthened after limiting the cohort to patients with more precise exposure assessment. Conclusion: Coronary patients exposed to TRAP are at increased risk of several types of cancer, particularly lung, prostate and breast. As these cancers are amenable to prevention strategies, identifying highly exposed patients may provide an opportunity to improve clinical care.